2008
DOI: 10.1109/tdei.2008.4591220
|View full text |Cite
|
Sign up to set email alerts
|

Surface-time enlargement law for gas breakdown

Abstract: This paper investigates, through theory and experiment, the applicability of the results obtained in laboratory tests of relatively short duration performed on model structures, as a part of the process of designing high-voltage equipment intended for lasting exploitation. Possibilities and limititions of applying these results to practical structures are examined using the methods of mathematical statistics. Special attention is devoted to the influence of electrode surface enlargement and pulse load (overvol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…However, the obtained statistical uncertainty, by the same procedure, shows that even for the random variable "flow rate" of the tritiated water it is also a deterministic quantity. This conclusion is correct with a statistical uncertainty less than 1%, so that the stochasticity of the random variable "flow rate" obtained by this method can be neglected [22,23].…”
Section: Resultsmentioning
confidence: 66%
“…However, the obtained statistical uncertainty, by the same procedure, shows that even for the random variable "flow rate" of the tritiated water it is also a deterministic quantity. This conclusion is correct with a statistical uncertainty less than 1%, so that the stochasticity of the random variable "flow rate" obtained by this method can be neglected [22,23].…”
Section: Resultsmentioning
confidence: 66%
“…where p n is the probability of breakdown occuring during the ½t 0 ; t n interval, and p 1i is the probability of breakdown occuring during the ½t i ; t iþ1 subinterval. 11,12) By considering probability distribution functions instead of discrete probabilities, 2) eq. ( 1) transforms into…”
Section: Time Enlargement Lawmentioning
confidence: 99%
“…3) It can be shown that double-exponential distribution is the most adequate for the breakdown time random variable. 12) The double-exponential distribution is a two-parameter distribution, and is thus easier to implement than the threeparameter Weibull distribution. By inserting the doubleexponential distribution function, given as…”
Section: Time Enlargement Lawmentioning
confidence: 99%
“…wing to outstanding insulating characteristics and arc-quenching capacity, the Sulfur hexafluoride (SF 6 ) gas has been widely used in extra/ultra-high voltage power transmission systems [1][2][3][4][5]. Usually, SF 6 gas is pressurized [6] in the electrical equipment to improve its capacitance and insulation performance because the heat capacity and dielectric strength increase with the pressure increase of SF 6 .…”
Section: Introductionmentioning
confidence: 99%